Squamous cell carcinoma: variation on dermatoscopy vascular features between well and non-well differentiated tumors - John Pyne (Mattioli1885, 2012)
Objective: Compare the dermatoscopy vascular features of well differentiated with non-well differentiated squamous cell carcinoma (SCC).